Moderate effect of phenolic and alkaloid compounds extracted from Brassica oleracea var. capitata leaf on blood glucose level in alloxan-induced diabetic rabbits - Khalid Abdulkareem Mohammed; Abbas Dawwas Mattar Al-Maliki (World Journal of Experimental Biosciences, 2014)
Diabetes mellitus is common metabolic disease and present all over the world with high ration. Herbal drugs against this disease are highly interesting and effective in recent years. In current study, we try to evaluate the effect of phenolic and alkaloid compounds on blood glucose level in experimental animals. Here, the water extracted of Brassica oleracea var. capitata leaf was ran in GC-Mass to identify the chemical compounds of water extract. The results of GC-Mass identified 18 compounds, from these compound one phenolic compound (Hydroquinone, acetate) and one alkaloid compound [Pyrrolidine, 1-(1-cyclohexen-1-yl)-] were found. In present study, alloxan-induced diabetic rabbits were prepared by injecting rabbit with three doses of alloxan. The alloxan-induced diabetic rabbits were administrated orally with either 0.3 gm/kg phenolic compound or 0.3 gm/kg alkaloid compound. The best results of blood glucose reduction were found when the diabetic rabbits administrated with phenolic compound. The significant reduction of glucose was observed post 4 h. While, the significant reduction of glucose was observed post 24 h in diabetic rabbits that administrated with alkaloid compound. It can be concluded from present study, the phenolic compound that extracted from Brassica oleracea var. capitata leaf was highly effective to reduce glucose as compared with alkaloids.
Keywords: Alkaloid [Pyrrolidine, 1-(1-cyclohexen-1-yl)-], Alloxan, Diabetic rabbits, Phenol (Hydroquinone, acetate).